2013
DOI: 10.1124/mol.113.084863
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-Induced Structural Plasticity in Mesencephalic Dopaminergic Neurons Is Mediated by Dopamine D3 Receptors and Akt-mTORC1 Signaling

Abstract: Although long-term exposure to nicotine is highly addictive, one beneficial consequence of chronic tobacco use is a reduced risk for Parkinson's disease. Of interest, these effects both reflect structural and functional plasticity of brain circuits controlling reward and motor behavior and, specifically, recruitment of nicotinic acetylcholine receptors (nAChR) in mesencephalic dopaminergic neurons. Because the underlying cellular mechanisms are poorly understood, we addressed this issue with use of primary cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
85
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 59 publications
11
85
0
Order By: Relevance
“…We found that ANA-12 reversed ethanol intake both in the two-bottle choice and DID paradigms and strongly decreased the expression of D 3 R in the striatum of WT-treated mice. Recently, D 3 R on VTA-SN dopaminergic neurons were found to mediate neuroplasticity effects of several addictive drugs (Collo et al , 2012; Collo et al , 2013). Therefore, our conclusion about the engagement of striatal RACK1, BDNF, and D 3 R in mediating ethanol consumption may be only a part of a more complex mechanism, whose elucidation may require an assessment of the effects of ethanol intake in the VTA-SN dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…We found that ANA-12 reversed ethanol intake both in the two-bottle choice and DID paradigms and strongly decreased the expression of D 3 R in the striatum of WT-treated mice. Recently, D 3 R on VTA-SN dopaminergic neurons were found to mediate neuroplasticity effects of several addictive drugs (Collo et al , 2012; Collo et al , 2013). Therefore, our conclusion about the engagement of striatal RACK1, BDNF, and D 3 R in mediating ethanol consumption may be only a part of a more complex mechanism, whose elucidation may require an assessment of the effects of ethanol intake in the VTA-SN dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In utero exposure of embryos to nicotine results in an increase in the soma size of DA neurons of newborn mice. This effect is mediated by dopamine D 3 receptors and recruitment of ERK/Akt/ mTORC1 signaling (53). In mouse lines with a deletion of the mTORC2 component Rictor in the entire CNS or in Purkinje cells, neurons are smaller and exhibit an abnormal morphology (283).…”
Section: Neurogenesis Brain Cell Differentiation and Morphogenesismentioning
confidence: 99%
“…Studies of cancer pathogenesis have shown that the activation of the ERK1/2 and PI3K/PKB signaling pathways plays an important role in the process of ECM deposition of turmor cells. Inhibitors such as PD98059 and LY294002 can promote apoptosis, reduce their biological activities and inhibit the conversion of cellular phenotype by inhibiting the deposition of ECM in malignant mesothelioma cells 6,22,23 . Another study found that the increased expression of fibronectin protein in rat mesangial cells was related to glomerular fibrosis and sclerosis…”
mentioning
confidence: 99%